A Novel Parvovirus Associated with the Whitefly Bemisia tabaci - Gousi, Fani; Belabess, Zineb; Laboureau, Nathalie; Peterschmitt, Michel; Pooggin, Mikhail M. (Pathogens (Basel), 2025)
The whitefly Bemisia tabaci (Hemiptera: Aleyrodoidea) causes direct feeding damage to crop plants and transmits pathogenic plant viruses, thereby threatening global food security. Although whitefly-infecting RNA viruses are known and proposed as biocontrol agents, no insect DNA virus has been found in any member of Aleyrodoidea. Using rolling circle amplification (RCA) of viral DNA from whiteflies collected from crop fields in Morocco, followed by Illumina sequencing of the RCA products, we found a novel insect single-stranded (ss) DNA parvovirus (family Parvoviridae) in addition to plant ssDNA geminiviruses transmitted by whiteflies. Based on its genome organization with inverted terminal repeats and evolutionarily conserved proteins mediating viral DNA replication (NS1/Rep) and encapsidation (VP), encoded on the forward and reverse strands, respectively, we named this virus Bemisia tabaci ambidensovirus (BtaDV) and classified it as a founding member of a new genus within the subfamily Densovirinae. This subfamily also contains three distinct genera of ambisense densoviruses of other hemipteran insects (Aphidoidea, Coccoidea, and Psylloidea). Furthermore, we provide evidence for the genetic variants of BtaDV circulating in whitefly populations and for its partial sequences integrated into the B. tabaci genome, with one integrant locus potentially expressing a fusion protein composed of viral Rep endonuclease and host DNA-binding domains. This suggests a long-term virus-host interaction and neofunctionalization of BtaDV-derived endogenous viral elements.